SISTEM INFORMASI REKAM MEDIS PADA RSIA PURI BUNDA MALANG BERBASIS WEB - Sartika Dewi Lestari; Mochamad Husni; Dian Wahyuningsih (Sekolah Tinggi Manajemen Informatika & Komputer PPKIA Pradya Paramita Malang, 2025)
Medical record systems in RSIA Puri Bunda Malang currently using decentralized storage systems, namely the separation between file inpatients and outpatients. Medical record system that exists today is assisted by using Microsoft Excel so that between outpatient and inpatient care can not process data simultaneously and allows the numbering doubles as the number owned by two different owners or the owners have two different numbers, in addition to the patients who come often forgot to take control of the patient's card or cards reason lost control patients. This leads to medical records clerk overwhelmed. The establishment of medical record information system on RSIA Puri Bunda Malang to help the performance of web-based medical record officers in improving patient care. System development method applied in this research is the development of the system (SDLC) Software Development Life Cycle waterfall model. Research Medical Record Information System In RSIA Puri Bunda Malang-based WEB is to reduce the double numbering error is equipped with a report that can be used as a reference for decision making or policy for the hospital.